Antifungal, anticancer, and docking studies of colchiceine complexes with monovalent metal cation salts. (2nd September 2019) - Kurek, Joanna; Kwaśniewska‐Sip, Patrycja; Myszkowski, Krzysztof; Cofta, Grzegorz; Barczyński, Piotr; Murias, Marek; Kurczab, Rafał; Śliwa, Paweł; Przybylski, Piotr
Abstract: Complexes of colchiceine with monovalent cation perchlorates and iodides have been obtained and characterized by spectroscopic methods. DFT and spectroscopic studies reveal that the dihedral angle ω1‐1a‐12‐12a, crucial for colchicine biological mechanism of action, that is, binding to tubulins depends on the diameter of the complexed metal cation. Biological tests indicated no antifungal properties of colchicine (it was active only toward A.pullulans ), in contrast to its derivative—(colchiceine). Complexation of colchiceine with metal cations improved significantly the antifungal potency, even below MIC <1 μg/ml. The colchiceine complexes were more potent than colchiceine, and some of them were even more potent than the fungicidal standard IPBC. The highest potency of colchiceine complexes was noted against A. pullulans (MIC = 0.5 μg/ml). In contrast to the findings concerning antifungal potency, the anticancer studies showed complexes of colchicine more active ( IC50 = 2 nM) than those of colchiceine ( IC50 = 6 μM). MDA‐MB‐231 breast cancer cell lines and human lung fibroblasts CCD39Lu were also tested. Abstract : Complexes of colchiceine with the respective monovalent cation have been obtained and characterized by spectroscopic methods, DFT study, and docking molecular modeling. Fungicidal and cytotoxic activity of colchicine complexes and colchiceine complexes were tested. Colchicine complexes showed to be active against SKOV‐3 cancer cell line, and colchiceine complexes showed promising fungicidal activity especially against A. pullulans .